Talento humano y responsabilidad social en el sector turístico hotelero en Cartagena de India Colombia (2019)
The research is based on the analysis, and description of the scenarios of human talent and social responsibility in the hotel tourism sector in Cartagena, will lead to understand the scope of social responsibility and human talent in the city, and establish a possible model of These elements can improve the management carried out by the tourism sector in order to achieve levels of weighting, evaluation and formulation of their practices in an authentic manner and that generates added value by focusing as a strategic activity, with high incidence and social impact in the cultural sine of the society and in a vital sector for the city as it is the tourism and that corresponds in the solution of socioeconomic problems from the organizational scope; hence its importance.